2022
DOI: 10.1101/2022.06.30.498172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of polarity regulators initiates gasdermin E mediated pyroptosis in human maternal fetal interface trophoblasts

Abstract: The syncytiotrophoblast is a single giant multinucleate epithelial cell that forms the maternal surface of the human placenta and is bathed in maternal blood. It acts as a physical barrier between the maternal and fetal compartments and facilitates nutrient and waste exchange. As such, syncytiotrophoblast dysfunction is a key feature of pregnancy pathologies, such as preeclampsia. An understudied feature of dysfunctional syncytiotrophoblast is the loss of apical microvilli. But a paucity of data exists about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
1
0
0
Order By: Relevance
“…Consistent with the findings in our in vitro model, anti-ezrin signal variably localized to the apical surface of individual vCT and, as previously reported, in a discontinuous pattern at the apical surface of the ST (Fig. 3C) (Berryman et al, 1993; Patel et al, 2023). Therefore, we confirmed that apical microvilli are present in a subset of vCT in the first trimester placenta.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with the findings in our in vitro model, anti-ezrin signal variably localized to the apical surface of individual vCT and, as previously reported, in a discontinuous pattern at the apical surface of the ST (Fig. 3C) (Berryman et al, 1993; Patel et al, 2023). Therefore, we confirmed that apical microvilli are present in a subset of vCT in the first trimester placenta.…”
Section: Resultssupporting
confidence: 92%